(untitled) (Al-Academy, 2021)
Current research targeted: Recognizing the impact of the differentiated education strategy on the achievement of the students of the Institute of Fine Arts / Diyala, for the academic year (2018-2019). The researcher used the experimental approach designed by two groups (control - experimental) and with a post-test to achieve the goal of the research, and the research sample was chosen from students of the fourth stage for the academic year (2018-2019). The sample was distributed randomly into two groups, the first experimental consisting of (30) students who studied using the differentiated education strategy, and the second control group consisting of (30) students who studied using the traditional method. The researcher prepared an achievement test that measures the level of theoretical and technical information about aesthetics subject through objective questions divided into (30) test items with one (score) for the correct answer and (zero) for the wrong or abandoned answer. The study found the effectiveness of using the differentiated education strategy in raising the level of achievement of the fourth stage students at the Institute of Fine Arts in the subject of aesthetics